STUDY OF ANTIBACTERIAL AND ANTIFUNGAL EFFECT OF THE ESSENTIAL OILS OF CHENOPODIUM AMBROSIOIDES L. AND ROSMARINUS OFFICINALIS L. - MAMMAD ZINEB; TORMAL DJASSINRA; KRIBII ABDERAHIM; OUNINE KHADIJA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This work looks at the valuation of two medicinal plants growing wild in the region of Gharb (Chenopodium ambrosioides L. and Rosmarinus officinalis L.) through the study of their antibacterial and antifungal effects vis-à-vis Xanthomonas fragariae, Pseudomonas aeruginosa, Staphylococcus aureus, and two fungal strains; Fusarium solani and Botrytis cinerea. Methods: The extraction of essential oils from each plant was carried out by hydrodistillation in a Clevenger-type apparatus. The antibacterial and antifungal tests of essential oils are carried out according to the method of diffusion using sterile discs (or aromatograms). Results are expressed in inhibition areas. Results: Antibacterial activity of essential oil of R. officinalis L. is best compared to that of C. ambrosioides L. with an area of inhibition that is shared by 1661.06 and 1384.74, respectively, for bacteria X. fragariae and P. aeruginosa, while this area is between 2122.64 and 2826 mm2 for F. solani and B. cinerea. Moreover, the essential oils of these two plants by the method of disk diffusion feature a very significant inhibitory effect on X. fragariae and P. aeruginosa, whereas they have no effect on S. aureus. Conclusion: The essential oils of C. ambrosioides L. and R. officinalis L. could be used as preservatives in food, to protect them from microbial or fungal spoilage.